On the investment potential of Sub-Saharan Africa: Уровень инвестиционного потенциала стран Африки к югу от Сахары: роль краудфандинга и венчурных инвестиций (Journal of Economic Research & Business Administration, 2023)
The study considers that the countries of the region are trying to take advantage of the opportunity of the Fourth Industrial Revolution (4IR) to industrialize and diversify their economies due to the rapid spread and widespread use of the Internet in the region. The modified methodology was used to assess the level of innovation potential (hereinafter referred to as IP), using elements such as the level of receptivity and readiness for innovative development, potential opportunities and others.Taking into account the role of financial opportunities in the development of innovations, a regression analysis was carried out, which indicates a direct link between IP and investment in R&D in these countries, on the basis of which the potential for innovative development is predicted for 5 years. The article assessed the possibility of financing African startups and SMEs through crowdfunding platforms and venture investments. The results show that the current Internet penetration contributes to the development of venture capital and crowdfunding, which will increase by 50% and 93%, respectively, by 2025. To achieve these results, the authors have developed a recommendation that can increase the financial capacity of sub-Saharan Africa for their innovation sector.